Dari Kewajiban Administratif Menuju Pengambilan Kebijakan Berbasis Data: Menguatkan Peran Evaluasi di Direktorat Jenderal Bimbingan Masyarakat Kristen - Deivy Donna Ingrid Supit (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article aims to analyze fundamental problems in integrating evaluation results into the planning, decision-making, and budgeting processes at the Directorate General of Christian Community Guidance. The main problems identified are the lack of binding internal regulations, exacerbated by an evaluation paradigm that is still oriented towards administrative fulfillment, as well as inadequate systems and human resource capacity. This condition causes evaluations to not function as a strategic pillar, but rather cease to function as archival reports. This paper uses qualitative methods with a descriptive analysis approach, USG (Urgency, Seriousness, Growth) analysis, and William N. Dunn's theory to identify the root of the problem and formulate solutions. Based on this analysis, several complementary policy alternatives are proposed, including the issuance of a Circular Letter requiring the use of evaluation results as a prerequisite for planning, the establishment of comprehensive Evaluation Implementation Standard Guidelines, and the development of Data Governance Guidelines and the utilization of technology. This policy is expected to encourage bureaucratic transformation, increase accountability, and ensure that every program and budget at the Directorate General of Christian Community Guidance is based on in-depth analysis, so that it can respond to the needs of the congregation more effectively and adaptively.